Efficacy of usage of pneumococcal 7-valent vaccine in prophylaxis of pneumococcal infection in Novosibirsk children from risk groups - O. A. Beletskaya; Yu.N. Gorbatykh; A. N. Shmakov; N. Yu. Ishalina; T. Yu. Ivleva; N. V. Kukhtinova ("Paediatrician" Publishers LLC, 2013)
In order to prevent children morbidity and mortality 116 children aged from 6 months to 5 years from 2 risk groups (1 - with bronchial-pulmonary dysplasia and 2 - with congenital heart defects) were vaccinated with pneumococcal 7-valent conjugated vaccine in 2011 at the expense of municipal budget. Among 116 children from both groups 16 (14%) have had community-acquired pneumonia, which is 22 times higher than in general children population in this region. Dynamic 1-year follow-up showed significant decrease of community-acquired pneumonia prevalence in risk groups: from 16/116 (14%) to 1/75 (1%) (p =0,006). There were no cases of invasive pneumococcal infections among vaccinated children and in 87,5% of them the general morbidity decreased. The frequency of moderate general post-vaccinal reactions was 1,8%, topical reactions - 0,9%. There were no other side effects during post-vaccinal period. Thereafter, the vaccination against pneumococcal infection performed in Novosibirsk in children with risk of fatal complications showed high efficacy and safety of the used vaccine.